Nonlinear and Complex Dynamics Applications in Physical, Biological, and Financial Systems - Machado, José António Tenreiro; Baleanu, Dumitru; Luo, Albert C. J. (Springer New York : Imprint: Springer, 2011)
Nonlinear Dynamics and Complex Systems describes chaos, fractal, and stochasticities within celestial mechanics, financial systems, and biochemical systems. Part I discusses methods and applications in celestial systems and new results in such areas as low energy impact dynamics, low-thrust planar trajectories to the moon and earth-to-halo transfers in the sun, earth and moon. Part II presents the dynamics of complex systems including bio-systems, neural systems, chemical systems, and hydro-dynamical systems. Finally, Part III covers economic and financial systems including market uncertainty, inflation, economic activity, and foreign competition and the role of nonlinear dynamics in each. The book also: Presents, for the first time in one volume, methods and applications that can be used to analyze celestial systems Shows how nonlinear dynamics can be used to analyze complex biological systems and address problems such as waste disposal, the biological impact of transportation systems on oceans, and predicting climate zone fluctuations and potential impacts on farming and other agricultural activities Discusses the role that dynamics and complex systems play in the economic and financial systems especially as related to inflation, international markets and uncertainty Nonlinear Dynamics and Complex Systems is an ideal book for scholars, researchers, and advanced technical members of industrial laboratory facilities interested in using nonlinear physics and mathematics to develop new tools and products.